Bibliometric analysis of consumer ethnocentrism and consumer racism with Islamic elements - Abdul Latif, Samshul Amry; Mohamad Ali, Afiza; Mohd Farudz, Baiduri Zaiyanna; Putra, Halim Dwi (Penerbit UiTM, 2025)
This study examines consumer ethnocentrism and consumer racismliterature with Islamic elements, employing bibliometric analysisthrough the Bibliometrix software to analyse current research trendsand identify emerging themes. Retrieving 101 publications with1,277 overall citations from the Scopus database, this study exploresthe structure and evolution of consumer ethnocentrism andconsumer racism. Three bibliometric analyses were conducted,including citation analysis, co-citation analysis, and keyword co-occurrence analysis, to reveal past, present, and future researchtrajectories. The study identifies two significant research streams:the interplay between consumer ethnocentrism and cultural identity,and the impact of consumer racism on purchasing behaviour inIslamic markets. Additionally, the findings highlight the increasingglobal interest in consumer ethnocentrism and consumer racism withIslamic elements, with contributions from 35 countries includingChina, Canada, India, Turkey, and Indonesia, and underscore theneed for high-quality research that addresses the complexities ofconsumer behaviour in diverse cultural contexts. This studycontributes to the theoretical understanding of consumerethnocentrism and consumer racism with Islamic elements,emphasizing the importance of quality over quantity in academicpublications. It also suggests directions for future research to furtherexplore the intersectionality of these concepts with broader socialissues. As one of the first studies to apply bibliometric analysis tothe fields of consumer ethnocentrism and consumer racism withIslamic elements, this research provides valuable insights intosignificant issues and emerging trends, paving the way for futurescholarly inquiry.